Control of cardiomyocyte differentiation timing by intercellular signaling pathways. (October 2021) - Rowton, Megan; Guzzetta, Alexander; Rydeen, Ariel B.; Moskowitz, Ivan P.
Abstract: Congenital Heart Disease (CHD), malformations of the heart present at birth, is the most common class of life-threatening birth defect (Hoffman (1995) [1], Gelb (2004) [2], Gelb (2014) [3] ). A major research challenge is to elucidate the genetic determinants of CHD and mechanistically link CHD ontogeny to a molecular understanding of heart development. Although the embryonic origins of CHD are unclear in most cases, dysregulation of cardiovascular lineage specification, patterning, proliferation, migration or differentiation have been described (Olson (2004) [4], Olson (2006) [5], Srivastava (2006) [6], Dunwoodie (2007) [7], Bruneau (2008) [8]). Cardiac differentiation is the process whereby cells become progressively more dedicated in a trajectory through the cardiac lineage towards mature cardiomyocytes. Defects in cardiac differentiation have been linked to CHD, although how the complex control of cardiac differentiation prevents CHD is just beginning to be understood. The stages of cardiac differentiation are highly stereotyped and have been well-characterized (Kattman et al. (2011) [9], Wamstad et al. (2012) [10], Luna-Zurita et al. (2016) [11], Loh et al. (2016) [12], DeLaughter et al. (2016) [13]); however, the developmental and molecular mechanisms that promote or delay the transition of a cell through these stages have not been as deeply investigated. Tight temporal control of progenitor differentiation is critically important for normal organ size, spatial organization, and cellular physiology and homeostasis of all organ systems (Raff et al. (1985) [14], Amthor et al. (1998) [15], Kopan et al. (2014) [16] ). This review will focus on the action of signaling pathways in the control of cardiomyocyte differentiation timing. Numerous signaling pathways, including the Wnt, Fibroblast Growth Factor, Hedgehog, Bone Morphogenetic Protein, Insulin-like Growth Factor, Thyroid Hormone and Hippo pathways, have all been implicated in promoting or inhibiting transitions along the cardiac differentiation trajectory. Gaining a deeper understanding of the mechanisms controlling cardiac differentiation timing promises to yield insights into the etiology of CHD and to inform approaches to restore function to damaged hearts.